Pendidikan Karakter Melalui Pendekatan Sufistik pada Mata Pelajaran Akidak Akhlak di Madrasah Aliyah Al-Hikmah Sumelap Tasikmalaya - Nasruloh, Ahmad; Nurzaman, Nurzaman (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2017)
The approach of Islamic mysticism in the subjects of Akidah Akhlak in the context of character education is very necessary, because the subjects of Akidah Akhlak also contain elements of Sufism. The use of the Islamic mysticism approach to these subjects is believed to strengthen and strengthen these subjects in building the character of superior learners. The results of this qualitative study show: First, the planning of character education education through the approach of Islamic mysticism in the subject Akhlak Madrasah Aliyah Al-Hikmah Tasikmalaya is based on Guidelines for Formulation of Curriculum Learning Plan 2013 as outlined in the Lesson Plans Program (RPP) which has several components, namely the identity, core competence (KI), basic competence (KD) and indicators of achievement of competence, learning objectives, learning materials, learning methods, learning media, learning resources, learning steps, and assessment of learning outcomes. Sufistic values ​​are included in basic competency components, competency achievement indicators, learning objectives, learning materials, learning methods, learning resources, and learning steps. Second, the implementation of character education through the Sufi approach on subjects Akhlak in MA Al-Hikmah Tasikmalaya covers the material and learning method. Sufism materials that are integrated into the subjects of Akidah Akhlak include zuhud, sabar, ridla, tawakkal, wara', tawadlu. Meanwhile, the teaching method used by the teacher is the method of advice, story method, and method of habituation. Third, character education through Sufi approach on subjects Akhlak in MA Al-Hikmah Tasikmalaya managed to maintain and improve the character or morals of learners, so that students in this madrasah relatively able to maintain the attitude and actions, and do not face the problem of juvenile delinquency